NALISIS PENGARUH TINGKAT PENDIDIKAN, PENGANGGURAN, DAN PDRB TERHADAP KEMISKINAN DI KARESIDENAN KEDU TAHUN 2014-2017 - Indrian Cahaya Putri; Whinarko Juliprijanto; Yustirania Septiani (DINAMIC : Directory Journal of Economic, 2020)
This study aims to analyze the influence of the level of education, unemployment, andGRDP on poverty in the Ex-Residence of Kedu in 2014-2017. The type of data in this studyuses secondary data from government agencies involved in 2014-2017. The data used in theform of education, unemployment, and GRDP from 2014-2017. The analysis model used ispanel data regression with the help of the Eviews 9. The results of the regression analysisshow that the level of education and unemployment have no significant effect on poverty.While the GRDP has a significant influence on poverty in the Ex-Residence of Kedu. Theresults of this study also show that together the level of education, unemployment, and GRDPsignificantly influence poverty in the Ex-Residence of Kedu.